Outcrop-Scale Investigation of Geological and Soil Physical Controls on Slope Stability in the Semilir Formation - Vinni Lovita; Dzikru Aminulloh; Djoko Mulyanto; Devanda Ayu Lidya Permata Putri; Aldio Kresna Pambayu (BPFP Universitas Bengkulu, 2025)
Landslides are a major hazard in Indonesia’s volcanic terrains, where highly weathered pyroclastic rocks and intense rainfall frequently trigger slope failures. This study aims to identify geological, geomorphological, and soil physical factors controlling slope stability within the Semilir Formation of Gunungkidul, Yogyakarta. Field observations and laboratory analyses were conducted to compare outcrops affected by translational landslides with adjacent stable slopes. Key parameters include bedding orientation, soil bulk density, plasticity index, and water retention capacity. The results indicate that dip-slope bedding orientations strongly predispose slopes to translational failure, whereas counter-dip structures enhance stability. Landslide-prone slopes exhibit higher bulk density, lower plasticity, and reduced water-holding capacity, which accelerate saturation and decrease cohesion during intense rainfall. In contrast, stable slopes possess higher plasticity and greater water retention, often reinforced by vegetation roots. These findings highlight the combined role of geological structure and soil properties as reliable indicators of landslide susceptibility. The study’s novelty lies in its outcrop-scale comparative approach within a single volcanic formation, providing practical implications for slope management through vegetation reinforcement, improved drainage, and locally calibrated rainfall thresholds. Full text pdf